Washable embroidered textile electrodes for long-term electrocardiography monitoring - Ankhili, Amale (Array, 2019)
The improvement of human health condition is an important objective that remains relevant since the origin of human being. Currently, cardiovascular diseases are the first cause of death worldwide. For this reason, permanent real-time monitoring of heart activity (Electrocardiogram: ECG), its analysis and alerting of concerned person is a solution to decrease the death toll provoked by heart diseases. ECG signal of medical quality is necessary for permanent monitoring and accurate heart examining. It can be obtained from instrumented underwear only if it is equipped with high quality, flexible textile based electrodes guaranteeing low contact resistance between the skin and them. This work is therefore devoted to the design and test of wearable textile embroidered bands following defined protocol for ECG long-term monitoring. These bands were investigated in three configurations: band without any adding layer to protect lines between electrodes and the connector, band with lines protected by simple yarn, band with lines protected with thermoplastic polyurethane (TPU). Bands were worn around chest by healthy subjects in a sitting position and ECG signals were acquired by an Arduino-based device and assessed. Washability tests of connected underwear were carried out over 50 washing cycles in a domestic machine and by using a commercial detergent. Influence of encapsulation process on the electrical properties of textile electrodes during repetitive washing process has also been investigated and analyzed. All the ECG signals acquired and recorded have been reviewed by a cardiologist in order to validate their quality required for accurate diagnosis.